KETAHANAN TIGA JENIS KAYU UNTUK BANTALAN REL KERETA API TERHADAP JAMUR PERUSAK KAYU SECARA LABORATORIS - Djarwanto Djarwanto; Sihati Suprapti (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
Wood still performs as the main materials for railway sleepers, especially at their connected portions, cross and bridge. So far, wood has not yet been effectively substituded by other materials. However, wood based railway sleepers are susceptible to deterioration by the decaying fungi. This study examined, the decay resistance of three wood species i.e. bangkirai (Shorea laevis), meranti batu (Shorea platyclados) and rasamala (Altingia exelsa). Samples were evaluated against the decayingfungi in a laboratory experiment using DIN 52176-modified standard.Results indicated that bangkirai and meranti batu were classified resistance against fungalattacks (Class II), whereas, rasamala was categorized moderately resistant (Class III). The weight loss percentage of rasamala was higher than those of bangkirai and meranti batu. The ability of fungus to degrade certain wood was depended upon kinds of wood and fungus itself. Fungi with significant decay ability were Pycnoporus sanguineus HHB-324, Schizophyllum commune, Polyporus sp., Trametes sp. and Tyromyces palustris.The highest weight losses were recorded on samples exposed consecutively to Pycnoporussanguineus and Schizophyllum commune.